Antimony Uptake Systems in the Protozoan Parasite Leishmania and Accumulation Differences in Antimony-Resistant Parasites - Brochu, Christian (American Society for Microbiology, 2003)
The first line drug against leishmaniasis consists of pentavalent antimony [Sb(V)], but there is general belief that the active form of the metal is the trivalent form [Sb(III)]. In this study, we have quantified the accumulation of Sb(V) and Sb(III) in Leishmania by using inductively coupled plasma mass spectrometry. The accumulation was studied in three Leishmania species at various life stages, sensitive or resistant to antimony. Both Sb(III) and Sb(V) are accumulated in promastigote and amastigote parasites, but through competition experiments with arsenite, we found that the routes of entry of Sb(V) and Sb(III) are likely to differ in Leishmania. The level of accumulation of either Sb(III) or Sb(V), however, was not correlated with the susceptibility of wild-type Leishmania cells to antimony. This suggests that other factors may also be implicated in the mode of action of the drugs. In contrast to metal susceptibility, resistance to Sb(III) correlated well with decreased antimony accumulation. This phenotype was energy dependent and highlights the importance of transport systems in drug resistance of this protozoan parasite.